Pengaruh Metode Flash Card terhadap Kemampuan Membaca dan Kreativitas Verbal pada Anak Tunagrahita Ringan - Makasara, Hanis Ribut (Happiness: Journal of Psychology and Islamic Science, 2023)
This study aims to determine the effect of the flash card method on the reading ability of mild mentally retarded children at SLB Dharma Wanita Grogol Kediri, where the flash card method as a learning method can improve the reading and verbal abilities of mild mentally retarded children. In this study, the population was 85 students of SLB Dharma Wanita Grogol Kediri and the sample was 7 students with mild mental retardation. These 7 students became the research sample where the selection was based on the objectives of the research and the recommendations of the teacher and head of the SLB. This research is a quasi-experimental research with one group pretest-posttest design. The design of this study used a group of subjects who were subjected to treatment for a certain period of time, measurements were made before and after the treatment was given. The data analysis used in this study was the nonparametric Mann Whitney test. Based on this data analysis, it was concluded that there was an increase in the reading ability of mild mentally retarded children with Mean Rank pretest = 4.50 and posttest = 10.50 and there was no increase in the verbal creativity of mild mentally retarded children with Mean Rank pretest = 6.43 and posttest = 8 , 57. So it can be concluded that the flash card method affects the ability to read with Sig. 0.006 <0.05 and the flash card method has no effect on verbal creativity with Sig. 0.336 > 0.05.